Food allergy. Part II – Fish - Rudzki, Edward (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
In the paper the following questions are discussed: 1) epidemiology of fish sensitivity including particularity of symptoms in children and adult patients; 2) reaction to airborne fish particles; 3) hiden sources of fish; 4) clinical picture of fish allergy; 5) cross reactions between various species of fish; 6) parvalbumin as a cross-reactive allergen and other fish allergens; 7) allergic reactions to Anisakis simplex in patients with fish allergy.